Building locally-led climate adaptation: Rural Kenyan youth perspectives on equity and resilience - Petesch, Patti; Fisher, Eleanor; Almeida, Olivia Ebenstål; Hellin, Jon (International Rice Research Institute, 2024)
A study of the perspectives of young indigenous men and women in rural communities in Kenya shows that strong institutions for local governance, inclusive decision-making and collective action are key for social equity and climate adaptation. To achieve this, we need to: (1) invest in the capacities of stakeholders to promote locally-led climate and equity initiatives; (2) promote young women’s and men’s leadership and networks, together with inter-generational exchange of experiences; and (3) build strategies and partnerships that are responsive to locally-identified youth needs.